Inovasi Pelayanan Publik Setengah Hati: Studi Pelayanan Publik di SAMSAT Kota Yogyakarta - Wasisto Raharjo Jati (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
Paradigm shift in public services to be more transparent, accountable, and participatory encountered many obstacles at its implementation. Constraints are not only coming from the government officials but also from the people who do not fully believe in the improvement efforts being taken by the government. Taking the example of One Stop Service (Samsat) in the city of Yogyakarta, this paper presents a portrait of public service delivery that is still full of practices that are inconsistent with the principles of new public management.